Development of Line Intersect Method for Logging Residue Assessment of Teak - Sarah Andini; Ahmad Budiaman; Muhdin Muhdin (Institut Pertanian Bogor (IPB University), 2017)
Line intersect method (LIM) emerged as one of the effective and efficient post-harvesting assessment methods. LIM was being widely used to estimate logging residue of plantation forest in the temperate zone. This method has not been used in tropical forest plantations, including teak forests. The study was carried out to determine the best design of LIM for assessing logging residue in the teak plantation. The circular and rectangular plot was used in this study. A hundred percent logging residue inventory was carried out on each plot. Then, one and combination of two and three line intersects per plot were placed on each plot. Bias, precision and accuracy criteria were calculated in order to compare the designs. The study found that estimation of logging residue volume using LIM was biased and tended to overestimate. LIM design with two lines combination per plot was the best design for assessing logging residue of the teak plantation.